Diallyl Disulfide Suppresses Inflammatory and Oxidative Machineries following Carrageenan Injection-Induced Paw Edema in Mice - Hongxing Zhang; Chi Shang; Zhao Tian; Hatem K. Amin; Rami B. Kassab; Ahmed E. Abdel Moneim; Yingang Zhang (Mediators of Inflammation)
Diallyl disulfide (DADS) is the major organosulfur constituent in garlic, with a variety of pharmacological activities including antioxidant and anti-inflammatory. Here, we examined the potential antiedematous impact of DADS- versus carrageenan-mediated paw edema in mice. Carrageenan injection potentiated an inflammatory reaction as presented by the elevated serological C-reactive protein (CRP) levels and transcription of tumor necrosis factor-alpha (TNF-α, Tnfα), interleukin-1 beta (IL-1β, Il1b), interleukin-2 (IL-2, Il2), inducible nitric oxide synthase (iNOS), nitric oxide (NO), cyclooxygenase-2 (COX-2, Ptgs2), prostaglandin E2 (PGE2), monocyte chemoattractant protein-1 (MCP-1, Ccl1), nuclear factor kappa B (NF-κB), and myeloperoxidase (MPO) activity, while interleukin-10 (IL-10) was declined in the injured paw tissue. Additionally, carrageenan elevated lipid peroxidation in terms of malondialdehyde (MDA) and decreased glutathione content (GSH). Remarkably, DADS was found to inhibit the inflammatory signaling, suppressed the developed oxidative damage, and protected the histopathological alterations in the inflamed paw tissue in response to carrageenan injection. Our findings suggest that DADS could be used as an alternative therapy used to alleviate the pathophysiological changes associated with the genesis of paw edema through its potent anti-inflammatory and antioxidant impacts.